Efektivitas Program Potasium Terhadap Tekanan Darah Penderita Hipertensi Di Desa Bandung Diwek Jombang - Desy Siswi Anjar Sari; Siswati; Fitri Firranda (Jurnal Keperawatan Muhammadiyah, 2026)
Objective: This study aimed to determine the effectiveness of the POTASIUM (Pos Tensi untuk Umum) program on blood pressure control among patients with hypertension in Bandung Village, Diwek District, Jombang Regency. Methods: This study employed an analytical correlational design with a cross-sectional approach. The sample consisted of 31 health cadres selected using accidental sampling. The independent variable was the POTASIUM program, while the dependent variable was blood pressure in patients with hypertension. Data were collected through observation sheets, pretest–posttest questionnaires, and blood pressure measurements. Data analysis included univariate analysis using frequency distribution and bivariate analysis using the Wilcoxon test due to non-normal data distribution. Results: he results showed a significant improvement in participants’ knowledge after the implementation of the POTASIUM program. The proportion of respondents with good knowledge increased from 61.3% before the intervention to 93.5% after the intervention. Statistical analysis using the Wilcoxon test indicated a significant difference in knowledge scores before and after the intervention (p = 0.000). In addition, 58.1% of health cadres demonstrated good psychomotor skills in implementing the program. The POTASIUM program was effective in supporting blood pressure control among patients with hypertension through regular monitoring, health education, and physical activity.